FOREWORD FROM HANDLING EDITOR - 8TH EDITION - Sodri, Ahyahudin (Journal of Environmental Science and Sustainable Development, 2021)
We are delighted to present the 8th edition of JESSD, published in July 2022. We have selected eleven of the best articles for this edition that related with topic of Environmental Science and Sustainable Development.